The Effect of Foot Care Demonstration Education on the Knowledge of Type 2 Diabetes Mellitus Patients at the Tilongkabila Health Center - Nurzia Delasfebrila Marukai; Ita Sulistiani; Sitti Fatimah M. Arsad (Universitas Muhammadiyah Palu, 2026)
Type 2 Diabetes Mellitus is a chronic disease that has the potential to cause various complications, one of which is diabetic foot ulcers which can be prevented through proper foot care. However, the low level of knowledge of people with type 2 diabetes mellitus about foot care is still a problem in primary health services. Education using the foot care demonstration method is one of the effective promotive and preventive efforts to increase the knowledge of people with diabetes mellitus related to foot care. This study aims to determine the effect of foot care demonstration education on the knowledge of patients with type 2 Diabetes Mellitus at the Tilongkabila Health Center. This research uses a design Quasi Experiment with the One group pre-post test design. A sample of 33 respondents was selected using the purposive sampling. The research instrument used a foot care knowledge questionnaire adapted from Munali (2019). Data analysis using tests Wilcoxon Signed Rank Test. The results showed that there was an increase in respondents' knowledge after the intervention with a p-value = 0.000 (p < 0.05), which means that there is a significant difference in knowledge between before and after education. Demonstration education is effective in increasing respondents' knowledge because it involves direct observation of foot care practices, using simple aids that are easy to find, and delivered in language that suits the respondent's condition, thus facilitating understanding and strengthening the respondents' memory of the material provided.